Simulation Analysis for Consistent Path Identification to Refine the Network Lifetime - G. Vennila (Institute of Advanced Engineering and Science, 2017)
As the demand for Mobile Ad hoc Network (MANET) applications grows, so does their use of many essential services where node consistent and stability of the communication paths are of great importance. In this scheme, we propose Simulation Analysis for Consistent Path Identification to Refine the Network Lifetime (CPIR). This technique offers more stable path and transmits the data through the consistent nodes. This article is focused on protecting the route from the inconsistent node in mobile communications to improve the network performance and reduce the energy consumption in the network. The simulation results demonstrate that CPIR provided reduce the energy utilization and improved both the longer lifetimes and increased number of packets delivered.